Enhancing Corporate Governance in Multinational Companies through Legal Compliance Measures - Okeoghene Elebe; Chikaome Chimara Imediegwu; Opeyemi Morenike Filani; Andikan Udofot Umana; Muritala Omeiza Umar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This review paper explores the critical role of legal compliance in enhancing corporate governance within multinational companies (MNCs). It begins by examining the essential relationship between legal compliance and corporate governance, highlighting how adherence to legal frameworks influences governance structures and practices. The paper then delves into the unique challenges MNCs face in implementing compliance measures across diverse legal environments, including jurisdictional differences and cultural, political, and economic factors. Furthermore, the review outlines strategies for integrating legal compliance into corporate governance frameworks, emphasizing the importance of leadership, transparency, and accountability. The role of corporate governance codes, international standards, and technology in promoting compliance is also discussed. Finally, the paper looks ahead to the future of corporate governance and legal compliance, considering emerging trends, the impact of technological innovation, and the evolving regulatory landscape. Through continuous improvement and adaptation, MNCs can enhance their governance practices and maintain legal compliance, securing long-term success in the global market.